Big data in smart farming: Challenges and opportunities - Reddy, G P Obi; Dwivedi, B S; Chary, G Ravindra (Indian Farming, 2021)
Smart farming powered by trending technologies like AI with big data analytics, IoT, AI, ML and DL immensely helps in making farming smarter with good profit margins. In data-driven smart farming, big data access, the availability of quality data, big spatial data computation, spatial data integration, data privacy and rights to use data are some of the important challenges exists. On the other hand, immense opportunities exist in smart farming, which include sensors-based technologies to achieve increasing production or accurate inventories for sustainability. Farmers can access the facilities of greenhouse through dashboard and operations can be managed by using voice commands. In smart farming supply chain, use of big data was found to be immensely useful at all stages.